Modelagem formal de workflows a partir de uma metodologia para gestão de processos de negócio na saúde pública - Lins, André Gustavo Teixeira (2010)
The efficiency of Brazilian Public health policies relies on many variables such as advanced management of its business processes. However, the rules of these processes are often based on tacit specialist knowledge and eventually on erratic working methods which result in redundant data, static tasks and wasted company resources. In order to improve this scenario, process-aware information systems have shown their importance by implementing a more systemic vision of corporate work, especially for public administration where this is not very well known. In the light of this matter, we highlight the workflow management systems as one of the best solutions to correct such problems due to its skill in handling workflows, linking broken tasks and sharing resources. In addition to the process of business modeling, it is essential that this specification is visual, flexible and very accurate, promoting the application of analysis techniques which guarantee previous results, especially in critical activities such as patients treatment, investigation of epidemics, and health promotion for large groups of people. Based on these assumptions, this work aims to adopt the Workflow-nets, an extension of the Petri nets formalism, to the formal specification and implementation of analysis techniques such as validation, verification and simulation, guided by an iterative methodology for business process management heavily based on workflows. Besides the workflow specification and the new methodology presented, this work also develops a workflow system with a log extraction module for the application of Workflow Mining, a technique used to identify the gap between business models and workflow specifications. For the scope of this project, we identified the area of public health responsible for water quality management in Alagoas and its connection with one of the most worrying social problems of the state: the infantile mortality.